Inheritances and inequality within generations - Pascale Bourquin; Robert Joyce; David Sturrock (Institute for Fiscal Studies (IFS), 2020)
This report examines the inheritances that are likely to be received by those living in England who were born in the 1960s, 1970s and 1980s. We explore the age at which inheritances are likely to be received and the amounts that we expect to be inherited, focusing on key inequalities in each. All figures are in 2017-18 prices.
Keywords: 330; Erbe; Generationengerechtigkeit; Vermögensverteilung; Großbritannien